Hans Kelsen and the natural law tradition - Langford, Peter; Bryan, Ian.; McGarry, John (Law teacher) (Studies in Moral Philosophy, 2019)
Hans Kelsen and the Natural Law Tradition provides the first sustained examination of Hans Kelsen's critical engagement, itself founded upon a distinctive theory of legal positivism, with the Natural Law Tradition. This edited collection commences with a comprehensive introduction which establishes the character of Kelsen's critical engagement as a general critique of natural law combined with a more specific critique of representative thinkers of the Natural Law Tradition. The subsequent chapters are then devoted to a detailed analysis of Kelsen's engagement with prominent theorists from the Natural Law Tradition. The volume concludes with an exploration, focusing upon the delineation of a non-positivist legal theory in the debate between Robert Alexy and Joseph Raz, of the continued presence of Kelsenian legal positivism in contemporary legal theory.